Influence of Fine Structure on the Variations of Thermal and Mechanical Properties in Flax Fibers Modified with Different Alkaline Treatment Conditions. Issue 13 (1st December 2022) - Bahrami, Reza; Bagheri, Reza; Dai, Chunping
ABSTRACT: The alkaline treatment condition plays a crucial role in governing the ultimate properties of flax fibers. In this study, flax fibers were modified with mild alkalization and severe mercerization conditions to give fundamental insight into how the molecular-scale changes in cell wall fine structure and cellulose supramolecular structure can affect the macroscopic properties of fibers. SEM, FTIR, XRD, TGA, and DSC techniques were employed to characterize the variations in morphology, composition, crystalline structure, and thermal properties of fibers. Also, tensile tests evaluated their reinforcing performance in polypropylene-based composites. The results indicated that alkalization in 5% (w/v) NaOH solution preserved the tensile properties of fibers, shifted their thermal decomposition temperature from 198 to 254°C, and effectively decreased their moisture absorption content by 18%. The improvements primarily originate from the partial removal of noncellulosic constituents and promoted crystallinity of native cellulose Iβ structure. However, mercerization in 20% (w/v) solution significantly reduced the rigidity of fibers in the longitudinal direction. Furthermore, it decreased the moisture absorption only by 6% and shifted the thermal degradation to 275°C. The excessive elimination of noncellulosic constituents and the polymorphic transformation, which led to a weaker hydrogen bonding network in the cellulose II region, accounts for these changes.